Influence of Basalt Fiber on the Mechanical Properties and Deformation Failure of Concrete after High Temperature - Yujing Wang; Qian Ren; Jianghong Xu (Advances in Civil Engineering)
This study was conducted to investigate how high temperatures and the addition of basalt fiber influence the mechanical behavior and failure characteristics of concrete. Two types of concrete were prepared: basalt fiber concrete (BFC), containing 1.0% basalt fiber by mass, and ordinary concrete (OC), without any fiber addition. The high-temperature effects of 200, 400, 600, and 800°C were carried out, and the compressive strength test, variable angle shear test, and cyclic compression test were carried out. The results show that basalt fiber will not change the mechanical characteristics of concrete and the change trend of stress–strain curve with temperature. The mass loss rate of BFC is always lower than that of OC. With the increase in temperature, the compressive strength, elastic modulus, and deformation modulus of the two types of concrete gradually decrease, and the plastic strain and dissipation energy gradually increase. Basalt fiber delays the loss of compressive strength in concrete and significantly increases the elastic modulus and the ability to resist cyclic compression and shear. Basalt fiber enhances the cohesion and friction resistance between concrete particles, thereby improving the structural stability and shear resistance of concrete. The severe damage temperature range of OC is 200–400°C, and the severe damage temperature range of BFC is 400–600°C. Based on the Holmquist–Johnson–Cook model, the meso-deformation and failure processes of OC and BFC were analyzed by LS-DYNA software. It was found that OC showed obvious brittle failure characteristics. With the increase in temperature, basalt fiber began to oxidize and decompose, and the meso-failure form of BFC changed from pullout failure to fracture failure.